Jump to navigation Jump to search

General

Display information for equation id:math.233719.6 on revision:233719

* Page found: Parseval's theorem (eq math.233719.6)

(force rerendering)

Cannot find the equation data in the database. Fetching from revision text.

Occurrences on the following pages:

Hash: c36ca6cffe3dea7c2cec347f42685bd9

TeX (original user input):

 \sum_{n=0}^{N-1} | x[n] |^2  =   \frac{1}{N} \sum_{k=0}^{N-1} | X[k] |^2

TeX (checked):

\sum _{n=0}^{N-1}|x[n]|^{2}={\frac {1}{N}}\sum _{k=0}^{N-1}|X[k]|^{2}

LaTeXML (experimental; uses MathML) rendering

MathML (10.296 KB / 1.528 KB) :

n = 0 N - 1 | x [ n ] | 2 = 1 N k = 0 N - 1 | X [ k ] | 2 superscript subscript 𝑛 0 𝑁 1 superscript 𝑥 delimited-[] 𝑛 2 1 𝑁 superscript subscript 𝑘 0 𝑁 1 superscript 𝑋 delimited-[] 𝑘 2 {\displaystyle\sum_{{n=0}}^{{N-1}}|x[n]|^{2}={\frac{1}{N}}\sum_{{k=0}}^{{N-1}}% |X[k]|^{2}}
<math xmlns="http://www.w3.org/1998/Math/MathML" id="p1.1.m1.1" class="ltx_Math" alttext="{\displaystyle\sum_{{n=0}}^{{N-1}}|x[n]|^{2}={\frac{1}{N}}\sum_{{k=0}}^{{N-1}}%&#10;|X[k]|^{2}}" display="inline">
  <semantics id="p1.1.m1.1a">
    <mrow id="p1.1.m1.1.23" xref="p1.1.m1.1.23.cmml">
      <mrow id="p1.1.m1.1.23.1" xref="p1.1.m1.1.23.1.cmml">
        <mstyle displaystyle="true" id="p1.1.m1.1.23.1.1" xref="p1.1.m1.1.23.1.1.cmml">
          <munderover id="p1.1.m1.1.23.1.1a" xref="p1.1.m1.1.23.1.1.cmml">
            <mo largeop="true" movablelimits="false" symmetric="true" id="p1.1.m1.1.1" xref="p1.1.m1.1.1.cmml"></mo>
            <mrow id="p1.1.m1.1.2.1" xref="p1.1.m1.1.2.1.cmml">
              <mi id="p1.1.m1.1.2.1.1" xref="p1.1.m1.1.2.1.1.cmml">n</mi>
              <mo id="p1.1.m1.1.2.1.2" xref="p1.1.m1.1.2.1.2.cmml">=</mo>
              <mn id="p1.1.m1.1.2.1.3" xref="p1.1.m1.1.2.1.3.cmml">0</mn>
            </mrow>
            <mrow id="p1.1.m1.1.3.1" xref="p1.1.m1.1.3.1.cmml">
              <mi id="p1.1.m1.1.3.1.1" xref="p1.1.m1.1.3.1.1.cmml">N</mi>
              <mo id="p1.1.m1.1.3.1.2" xref="p1.1.m1.1.3.1.2.cmml">-</mo>
              <mn id="p1.1.m1.1.3.1.3" xref="p1.1.m1.1.3.1.3.cmml">1</mn>
            </mrow>
          </munderover>
        </mstyle>
        <msup id="p1.1.m1.1.23.1.2" xref="p1.1.m1.1.23.1.2.cmml">
          <mrow id="p1.1.m1.1.23.1.2.2" xref="p1.1.m1.1.23.1.2.2.1.cmml">
            <mo stretchy="false" id="p1.1.m1.1.4" xref="p1.1.m1.1.23.1.2.2.1.1.cmml">|</mo>
            <mrow id="p1.1.m1.1.23.1.2.2.2" xref="p1.1.m1.1.23.1.2.2.2.cmml">
              <mi id="p1.1.m1.1.5" xref="p1.1.m1.1.5.cmml">x</mi>
              <mo id="p1.1.m1.1.23.1.2.2.2.1" xref="p1.1.m1.1.23.1.2.2.2.1.cmml"></mo>
              <mrow id="p1.1.m1.1.23.1.2.2.2.2" xref="p1.1.m1.1.23.1.2.2.2.2.1.cmml">
                <mo stretchy="false" id="p1.1.m1.1.6" xref="p1.1.m1.1.23.1.2.2.2.2.1.1.cmml">[</mo>
                <mi id="p1.1.m1.1.7" xref="p1.1.m1.1.7.cmml">n</mi>
                <mo stretchy="false" id="p1.1.m1.1.8" xref="p1.1.m1.1.23.1.2.2.2.2.1.1.cmml">]</mo>
              </mrow>
            </mrow>
            <mo stretchy="false" id="p1.1.m1.1.9" xref="p1.1.m1.1.23.1.2.2.1.1.cmml">|</mo>
          </mrow>
          <mn id="p1.1.m1.1.10.1" xref="p1.1.m1.1.10.1.cmml">2</mn>
        </msup>
      </mrow>
      <mo id="p1.1.m1.1.11" xref="p1.1.m1.1.11.cmml">=</mo>
      <mrow id="p1.1.m1.1.23.2" xref="p1.1.m1.1.23.2.cmml">
        <mstyle displaystyle="true" id="p1.1.m1.1.12" xref="p1.1.m1.1.12.cmml">
          <mfrac id="p1.1.m1.1.12a" xref="p1.1.m1.1.12.cmml">
            <mn id="p1.1.m1.1.12.2" xref="p1.1.m1.1.12.2.cmml">1</mn>
            <mi id="p1.1.m1.1.12.3" xref="p1.1.m1.1.12.3.cmml">N</mi>
          </mfrac>
        </mstyle>
        <mo id="p1.1.m1.1.23.2.1" xref="p1.1.m1.1.23.2.1.cmml"></mo>
        <mrow id="p1.1.m1.1.23.2.2" xref="p1.1.m1.1.23.2.2.cmml">
          <mstyle displaystyle="true" id="p1.1.m1.1.23.2.2.1" xref="p1.1.m1.1.23.2.2.1.cmml">
            <munderover id="p1.1.m1.1.23.2.2.1a" xref="p1.1.m1.1.23.2.2.1.cmml">
              <mo largeop="true" movablelimits="false" symmetric="true" id="p1.1.m1.1.13" xref="p1.1.m1.1.13.cmml"></mo>
              <mrow id="p1.1.m1.1.14.1" xref="p1.1.m1.1.14.1.cmml">
                <mi id="p1.1.m1.1.14.1.1" xref="p1.1.m1.1.14.1.1.cmml">k</mi>
                <mo id="p1.1.m1.1.14.1.2" xref="p1.1.m1.1.14.1.2.cmml">=</mo>
                <mn id="p1.1.m1.1.14.1.3" xref="p1.1.m1.1.14.1.3.cmml">0</mn>
              </mrow>
              <mrow id="p1.1.m1.1.15.1" xref="p1.1.m1.1.15.1.cmml">
                <mi id="p1.1.m1.1.15.1.1" xref="p1.1.m1.1.15.1.1.cmml">N</mi>
                <mo id="p1.1.m1.1.15.1.2" xref="p1.1.m1.1.15.1.2.cmml">-</mo>
                <mn id="p1.1.m1.1.15.1.3" xref="p1.1.m1.1.15.1.3.cmml">1</mn>
              </mrow>
            </munderover>
          </mstyle>
          <msup id="p1.1.m1.1.23.2.2.2" xref="p1.1.m1.1.23.2.2.2.cmml">
            <mrow id="p1.1.m1.1.23.2.2.2.2" xref="p1.1.m1.1.23.2.2.2.2.1.cmml">
              <mo stretchy="false" id="p1.1.m1.1.16" xref="p1.1.m1.1.23.2.2.2.2.1.1.cmml">|</mo>
              <mrow id="p1.1.m1.1.23.2.2.2.2.2" xref="p1.1.m1.1.23.2.2.2.2.2.cmml">
                <mi id="p1.1.m1.1.17" xref="p1.1.m1.1.17.cmml">X</mi>
                <mo id="p1.1.m1.1.23.2.2.2.2.2.1" xref="p1.1.m1.1.23.2.2.2.2.2.1.cmml"></mo>
                <mrow id="p1.1.m1.1.23.2.2.2.2.2.2" xref="p1.1.m1.1.23.2.2.2.2.2.2.1.cmml">
                  <mo stretchy="false" id="p1.1.m1.1.18" xref="p1.1.m1.1.23.2.2.2.2.2.2.1.1.cmml">[</mo>
                  <mi id="p1.1.m1.1.19" xref="p1.1.m1.1.19.cmml">k</mi>
                  <mo stretchy="false" id="p1.1.m1.1.20" xref="p1.1.m1.1.23.2.2.2.2.2.2.1.1.cmml">]</mo>
                </mrow>
              </mrow>
              <mo stretchy="false" id="p1.1.m1.1.21" xref="p1.1.m1.1.23.2.2.2.2.1.1.cmml">|</mo>
            </mrow>
            <mn id="p1.1.m1.1.22.1" xref="p1.1.m1.1.22.1.cmml">2</mn>
          </msup>
        </mrow>
      </mrow>
    </mrow>
    <annotation-xml encoding="MathML-Content" id="p1.1.m1.1b">
      <apply id="p1.1.m1.1.23.cmml" xref="p1.1.m1.1.23">
        <eq id="p1.1.m1.1.11.cmml" xref="p1.1.m1.1.11"/>
        <apply id="p1.1.m1.1.23.1.cmml" xref="p1.1.m1.1.23.1">
          <apply id="p1.1.m1.1.23.1.1.cmml" xref="p1.1.m1.1.23.1.1">
            <csymbol cd="ambiguous" id="p1.1.m1.1.23.1.1.1.cmml" xref="p1.1.m1.1.23.1.1">superscript</csymbol>
            <apply id="p1.1.m1.1.23.1.1.2.cmml" xref="p1.1.m1.1.23.1.1">
              <csymbol cd="ambiguous" id="p1.1.m1.1.23.1.1.2.1.cmml" xref="p1.1.m1.1.23.1.1">subscript</csymbol>
              <sum id="p1.1.m1.1.1.cmml" xref="p1.1.m1.1.1"/>
              <apply id="p1.1.m1.1.2.1.cmml" xref="p1.1.m1.1.2.1">
                <eq id="p1.1.m1.1.2.1.2.cmml" xref="p1.1.m1.1.2.1.2"/>
                <ci id="p1.1.m1.1.2.1.1.cmml" xref="p1.1.m1.1.2.1.1">𝑛</ci>
                <cn type="integer" id="p1.1.m1.1.2.1.3.cmml" xref="p1.1.m1.1.2.1.3">0</cn>
              </apply>
            </apply>
            <apply id="p1.1.m1.1.3.1.cmml" xref="p1.1.m1.1.3.1">
              <minus id="p1.1.m1.1.3.1.2.cmml" xref="p1.1.m1.1.3.1.2"/>
              <ci id="p1.1.m1.1.3.1.1.cmml" xref="p1.1.m1.1.3.1.1">𝑁</ci>
              <cn type="integer" id="p1.1.m1.1.3.1.3.cmml" xref="p1.1.m1.1.3.1.3">1</cn>
            </apply>
          </apply>
          <apply id="p1.1.m1.1.23.1.2.cmml" xref="p1.1.m1.1.23.1.2">
            <csymbol cd="ambiguous" id="p1.1.m1.1.23.1.2.1.cmml" xref="p1.1.m1.1.23.1.2">superscript</csymbol>
            <apply id="p1.1.m1.1.23.1.2.2.1.cmml" xref="p1.1.m1.1.23.1.2.2">
              <abs id="p1.1.m1.1.23.1.2.2.1.1.cmml" xref="p1.1.m1.1.4"/>
              <apply id="p1.1.m1.1.23.1.2.2.2.cmml" xref="p1.1.m1.1.23.1.2.2.2">
                <times id="p1.1.m1.1.23.1.2.2.2.1.cmml" xref="p1.1.m1.1.23.1.2.2.2.1"/>
                <ci id="p1.1.m1.1.5.cmml" xref="p1.1.m1.1.5">𝑥</ci>
                <apply id="p1.1.m1.1.23.1.2.2.2.2.1.cmml" xref="p1.1.m1.1.23.1.2.2.2.2">
                  <csymbol cd="latexml" id="p1.1.m1.1.23.1.2.2.2.2.1.1.cmml" xref="p1.1.m1.1.6">delimited-[]</csymbol>
                  <ci id="p1.1.m1.1.7.cmml" xref="p1.1.m1.1.7">𝑛</ci>
                </apply>
              </apply>
            </apply>
            <cn type="integer" id="p1.1.m1.1.10.1.cmml" xref="p1.1.m1.1.10.1">2</cn>
          </apply>
        </apply>
        <apply id="p1.1.m1.1.23.2.cmml" xref="p1.1.m1.1.23.2">
          <times id="p1.1.m1.1.23.2.1.cmml" xref="p1.1.m1.1.23.2.1"/>
          <apply id="p1.1.m1.1.12.cmml" xref="p1.1.m1.1.12">
            <divide id="p1.1.m1.1.12.1.cmml" xref="p1.1.m1.1.12"/>
            <cn type="integer" id="p1.1.m1.1.12.2.cmml" xref="p1.1.m1.1.12.2">1</cn>
            <ci id="p1.1.m1.1.12.3.cmml" xref="p1.1.m1.1.12.3">𝑁</ci>
          </apply>
          <apply id="p1.1.m1.1.23.2.2.cmml" xref="p1.1.m1.1.23.2.2">
            <apply id="p1.1.m1.1.23.2.2.1.cmml" xref="p1.1.m1.1.23.2.2.1">
              <csymbol cd="ambiguous" id="p1.1.m1.1.23.2.2.1.1.cmml" xref="p1.1.m1.1.23.2.2.1">superscript</csymbol>
              <apply id="p1.1.m1.1.23.2.2.1.2.cmml" xref="p1.1.m1.1.23.2.2.1">
                <csymbol cd="ambiguous" id="p1.1.m1.1.23.2.2.1.2.1.cmml" xref="p1.1.m1.1.23.2.2.1">subscript</csymbol>
                <sum id="p1.1.m1.1.13.cmml" xref="p1.1.m1.1.13"/>
                <apply id="p1.1.m1.1.14.1.cmml" xref="p1.1.m1.1.14.1">
                  <eq id="p1.1.m1.1.14.1.2.cmml" xref="p1.1.m1.1.14.1.2"/>
                  <ci id="p1.1.m1.1.14.1.1.cmml" xref="p1.1.m1.1.14.1.1">𝑘</ci>
                  <cn type="integer" id="p1.1.m1.1.14.1.3.cmml" xref="p1.1.m1.1.14.1.3">0</cn>
                </apply>
              </apply>
              <apply id="p1.1.m1.1.15.1.cmml" xref="p1.1.m1.1.15.1">
                <minus id="p1.1.m1.1.15.1.2.cmml" xref="p1.1.m1.1.15.1.2"/>
                <ci id="p1.1.m1.1.15.1.1.cmml" xref="p1.1.m1.1.15.1.1">𝑁</ci>
                <cn type="integer" id="p1.1.m1.1.15.1.3.cmml" xref="p1.1.m1.1.15.1.3">1</cn>
              </apply>
            </apply>
            <apply id="p1.1.m1.1.23.2.2.2.cmml" xref="p1.1.m1.1.23.2.2.2">
              <csymbol cd="ambiguous" id="p1.1.m1.1.23.2.2.2.1.cmml" xref="p1.1.m1.1.23.2.2.2">superscript</csymbol>
              <apply id="p1.1.m1.1.23.2.2.2.2.1.cmml" xref="p1.1.m1.1.23.2.2.2.2">
                <abs id="p1.1.m1.1.23.2.2.2.2.1.1.cmml" xref="p1.1.m1.1.16"/>
                <apply id="p1.1.m1.1.23.2.2.2.2.2.cmml" xref="p1.1.m1.1.23.2.2.2.2.2">
                  <times id="p1.1.m1.1.23.2.2.2.2.2.1.cmml" xref="p1.1.m1.1.23.2.2.2.2.2.1"/>
                  <ci id="p1.1.m1.1.17.cmml" xref="p1.1.m1.1.17">𝑋</ci>
                  <apply id="p1.1.m1.1.23.2.2.2.2.2.2.1.cmml" xref="p1.1.m1.1.23.2.2.2.2.2.2">
                    <csymbol cd="latexml" id="p1.1.m1.1.23.2.2.2.2.2.2.1.1.cmml" xref="p1.1.m1.1.18">delimited-[]</csymbol>
                    <ci id="p1.1.m1.1.19.cmml" xref="p1.1.m1.1.19">𝑘</ci>
                  </apply>
                </apply>
              </apply>
              <cn type="integer" id="p1.1.m1.1.22.1.cmml" xref="p1.1.m1.1.22.1">2</cn>
            </apply>
          </apply>
        </apply>
      </apply>
    </annotation-xml>
    <annotation encoding="application/x-tex" id="p1.1.m1.1c">{\displaystyle\sum_{{n=0}}^{{N-1}}|x[n]|^{2}={\frac{1}{N}}\sum_{{k=0}}^{{N-1}}%
|X[k]|^{2}}</annotation>
  </semantics>
</math>

SVG (12.706 KB / 4.018 KB) :

sigma-summation Underscript n equals 0 Overscript upper N minus 1 Endscripts StartAbsoluteValue x times left-bracket n right-bracket EndAbsoluteValue squared equals StartFraction 1 Over upper N EndFraction times sigma-summation Underscript k equals 0 Overscript upper N minus 1 Endscripts StartAbsoluteValue upper X times left-bracket k right-bracket EndAbsoluteValue squared

MathML with SVG or PNG fallback (recommended for modern browsers and accessibility tools) rendering

MathML (0 B / 8 B) :

SVG image empty. Force Re-Rendering

SVG (0 B / 8 B) :


PNG (0 B / 8 B) :


Translations to Computer Algebra Systems

Translation to Maple

In Maple: sum((abs(x*[n]*))^(2), n = 0..N - 1)=(1)/(N)*sum((abs(X*[k]*))^(2), k = 0..N - 1)

Information about the conversion process:


Translation to Mathematica

In Mathematica: Sum[(Abs[x*[n]*])^(2), {n, 0, N - 1}]=Divide[1,N]*Sum[(Abs[X*[k]*])^(2), {k, 0, N - 1}]

Information about the conversion process:


Similar pages

Calculated based on the variables occurring on the entire Parseval's theorem page

Identifiers

MathML observations

0results

0results

no statistics present please run the maintenance script ExtractFeatures.php

0 results

0 results